2018
DOI: 10.1038/gim.2017.143
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent variants in OTOF are significant contributors to prelingual nonsydromic hearing loss in Saudi patients

Abstract: PurposeHearing loss is more prevalent in the Saudi Arabian population than in other populations; however, the full range of genetic etiologies in this population is unknown. We report the genetic findings from 33 Saudi hearing-loss probands of tribal ancestry, with predominantly prelingual severe to profound hearing loss.MethodsTesting was performed over the course of 2012–2016, and involved initial GJB2 sequence and GJB6-D13S1830 deletion screening, with negative cases being reflexed to a next-generation sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…The most common mutations in many populations are in the GJB2 gene, which encodes the connexin 26 protein, and cause severe-to-profound autosomal recessive NSHL 1 , 5 . Sanger sequencing of GJB2 was therefore performed in previous studies 6 , 7 . In the Saudi population, the OTOF gene, rather than GJB2 , was revealed to be a major and potential contributor to hearing loss 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The most common mutations in many populations are in the GJB2 gene, which encodes the connexin 26 protein, and cause severe-to-profound autosomal recessive NSHL 1 , 5 . Sanger sequencing of GJB2 was therefore performed in previous studies 6 , 7 . In the Saudi population, the OTOF gene, rather than GJB2 , was revealed to be a major and potential contributor to hearing loss 7 .…”
Section: Introductionmentioning
confidence: 99%
“…As the mutation spectrum of the OTOF gene shows great discrepancies between different countries and ethnic populations, including high frequencies of the mutation p.E1700Q in Chinese from Taiwan [5], p.R1939Q in Japanese [6, 17], p.Val1778Phe in Ashkenazi Jewish [18], Q829X in Spanish [19], c.2905-2923delinsCTCCGAG-CGCA in Argentinean [9], and p.R1792H in Saudi Arabian [20], understanding of the molecular mechanism of ANSD needs to be improved. Here, we report two novel compound heterozygous OTOF mutations in different Chinese families, which provide more information about the etiology of ANSD at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that OTOF mutation causes profound hearing loss. In a recent cohort study, OTOF was found to contribute most to AR hearing loss in the Saudi Arabian population, responsible for 21.1% (7/11) of cases in the study population [4]. Wang et al also reported that OTOF mutations cause mild, moderate, or profound hearing loss [2].…”
Section: Discussionmentioning
confidence: 87%
“…Hearing loss is characterized by any degree (mild, moderate, severe, or profound) of loss of the ability to hear that can occur at any stage of life [1,2]. Congenital hearing loss is the fourth highest cause of disability globally with a prevalence ranging from 0.2 to 1% among newborns worldwide [3,4]; currently, there are approximately 466 million people with hearing loss [5]. In Pakistan, hereditary deafness covers 70% of cases, and autosomal recessive hearing impairment accounts most due to the high rate of consanguineous marriages [6].…”
Section: Introductionmentioning
confidence: 99%